2017
DOI: 10.1111/bju.14062
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and robot‐assisted vs open radical prostatectomy for the treatment of localized prostate cancer: a Cochrane systematic review

Abstract: There is no evidence to inform the comparative effectiveness of LRP or RARP compared with ORP for oncological outcomes. Urinary and sexual quality of life appear similar. Overall and serious postoperative complication rates appear similar. The difference in postoperative pain may be minimal. Men undergoing LRP or RARP may have a shorter hospital stay and receive fewer blood transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 35 publications
4
72
0
4
Order By: Relevance
“…Because of the difficulties associated with conducting randomized trials, comparing outcomes related to RALP and RRP is challenging and studies have shown mixed results [21222324]. A Cochrane review [25], which is the most recent study on this issue, found no evidence supporting the effectiveness of RALP (in terms of oncological and functional outcome) over RRP. However, men undergoing RALP had shorter hospital stays and lower rates of blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulties associated with conducting randomized trials, comparing outcomes related to RALP and RRP is challenging and studies have shown mixed results [21222324]. A Cochrane review [25], which is the most recent study on this issue, found no evidence supporting the effectiveness of RALP (in terms of oncological and functional outcome) over RRP. However, men undergoing RALP had shorter hospital stays and lower rates of blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The reported benefits of RARP include less blood loss, lower blood transfusion rates, shorter hospital stay and earlier recovery from surgery compared with open prostatectomy . Nevertheless, the post‐operative course affecting QOL the most are urinary continence and sexual potency .…”
Section: Discussionmentioning
confidence: 99%
“…"No" indicates no erections, "Yes" indicates presence of erection. * represents significant difference between groups of patients with varying erection status 4 | DISCUSSIONThe reported benefits of RARP include less blood loss, lower blood transfusion rates, shorter hospital stay and earlier recovery from surgery compared with open prostatectomy 2,9,10. Nevertheless, the post-operative course affecting QOL the most are urinary continence and sexual potency 1,2.…”
mentioning
confidence: 99%
“…Few studies emphasized the safety of the laparoscopic approach and its benefits, which include shorter hospital stay, reduced blood loss, and postoperative pain compared to the open counterpart [1][2][3].…”
Section: Introductionmentioning
confidence: 99%